(untitled) (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2015)
We investigate the optical bistable behavior for a weakly interacting two-species Bose-Einstein condensates inside a pumped optical cavity by considering the two possible regimes- the phase mixed regime and the phase segregated regime. We find that the cavity-pump detuning plays a significant role in controlling the threshold of the optical bistability and the constrast between the bistability values depending upon the state we are working in. We also demonstrate the occurence of normal mode splitting in the optical spectrum for both the regimes which further showing the position and amplitude discrepancies in the spectral peaks.